Epidemiological observations of invasive group b streptococcus infections in six major hospitals in peninsular Malaysia - Muthanna, AbdulRahman; Mohd Deas, Mohd Nasir; Abdul Rahman, Nurul Asyikin; Dzaraly, Nurul Diana; Zainal Baharin, Nurul Hana; Aziz, Nur Afiza; Shan, Chua Hui; Ismail, Zalina (Wolters Kluwer Medknow Publications, 2024)
Objective: To address the lack of research on invasive group B Streptococcus (GBS) infections in Malaysia and Southeast Asia through a comprehensive analysis of GBS isolates obtained from hospitals. Methods: Medical records from patients with GBS infection isolated from the sterile site, such as blood and cerebrospinal fluid from 14 July 2019 to 15 December 2020, were reviewed from six major hospitals in Peninsular Malaysia. Inclusion criteria were invasive GBS, sterile sites and non-repeated GBS isolated from the same patients in the same admission. Viable isolates were re-identified for GBS and serotyped. Results: A total of 118 patients were eligible, with a majority of non-pregnant adults (76.3%). Over half of the patients (62.7%) had underlying medical conditions, with diabetes as the most common disease, followed by respiratory disease, renal disease, cardiovascular disease and skin and soft tissue disease. The most common manifestations were sepsis, followed by soft tissue abscess, diabetic foot ulcer, wet gangrene and cellulitis. The overall mortality was 7.6%. The most common serotype was serotype 桋. Conclusions: Invasive GBS infection among non-pregnant adults showed a rising trend, particularly among diabetic individuals. The study underscores the importance of reducing risk factors and highlights the necessity of developing GBS vaccination as a preventive strategy for both infants and adults.